ANALISA PERBEDAAN GENDER TERHADAP PERILAKU AKUNTAN PENDIDIK - Supartini, Supartini (Jurnal Analisis Bisnis Ekonomi, 2010)
Gender influence issue to behavior about attitude, motivation, diskrimination perseption and wish level job move rubber practis accountan already reseched by Hunton et.al (1996). This research to test influence gender diskrimination to educator accountant behaviour at private high institution in Surakarta. At Surakarta many private high institution and educator accountant. This research analysis gender diskrimination to educator accountant behaviour. Educator accountant behaviour having influence gender diskrimination associaed with attitude, moivation, diskrimination perception. Educator accountant behaviour at prvate high institutiont in Surakarta as the responden. Examination to hyphothesis this research use T-test statisic with use SPSS software. The result rever attitude, motivation, diskrimination perseption doesn't different significant about educator accountant man and educator accountant women.